Faktor-Faktor yang Memengaruhi Minat Sedekah Non Tunai - Narendra Irawati; Endah Nur Fitriyani (Journal of Islamic Economics and Finance Studies, 2022)
In this modern era, the development of Islamic financial instruments has entered an era of increasing awareness from various parties. One of them is by participating in adapting technological developments in alms collection, in addition to making it easier for almsgivers to channel their donations, this strategy is expected to optimize the potential of ZIS in Indonesia. However, the factors that encourage interest in non-cash donations still need to be studied more deeply in order to improve the optimization of ZIS collection. This study aims to determine the effect of perceptions of convenience, income, and religiosity on interest in non-cash alms with trust as a moderating variable. This study used a quantitative method by processing primary data collected from questionnaires given to 100 Muslim communities in the city of Salatiga who were used as research samples. The analytical tool used is multiple linear regression with the help of the SPSS 26 application. Data analysis methods include instrument testing, classical assumption testing, and hypothesis testing. The results of this study indicate that perceived convenience and income have a significant positive effect on interest in non-cash alms. Meanwhile, religiosity has no effect on interest in non-cash alms. As well as trust is able to moderate the effect of perceptions of convenience, income, and religiosity on interest in non-cash alms.Pada era modern seperti sekarang, perkembangan instrumen keuangan Islam telah memasuki era peningkatan kesadaran dari berbagai pihak. Salah satunya dengan turut mengadaptasi perkembangan teknologi dalam penghimpunan sedekah, selain memudahkan penyedekah menyalurkan donasinya, strategi tersebut diharapkan dapat mengoptimalisasi potensi ZIS yang ada di Indonesia. Namun, faktor yang mendorong minat berdonasi non tunai masih perlu dikaji lebih dalam agar mampu meningkatkan optimalisasi penghimpunan ZIS. Penelitian ini bertujuan untuk mengetahui pengaruh persepsi kemudahan, pendapatan, dan religiositas terhadap minat sedekah non tunai dengan kepercayaan sebagai variabel moderasi. Penelitian ini menggunakan metode kuantitatif dengan mengolah data primer yang dihimpun dari kuesioner yang diberikan kepada 100 masyarakat muslim kota Salatiga yang dijadikan sebagai sampel penelitian. Alat analisis yang digunakan adalah regresi linear berganda dengan bantuan aplikasi SPSS 26. Metode analisis data meliputi uji instrumen, uji asumsi klasik, dan uji hipotesis. Hasil penelitian ini menunjukkan bahwa persepsi kemudahan dan pendapatan berpengaruh positif signifikan terhadap minat sedekah non tunai. Sedangkan religiositas tidak berpengaruh terhadap minat sedekah non tunai. Serta kepercayaan mampu memoderasi pengaruh persepsi kemudahan, pendapatan, dan religiositas terhadap minat sedekah non tunai.